How do we know that we are free? - O’Connor, Timothy (Array, 2019)
We are naturally disposed to believe of ourselves and others that we are free: that what we do is often and to a considerable extent ‘up to us’ via the exercise of a power of choice to do or to refrain from doing one or more alternatives of which we are aware. In this article, I probe thesource and epistemic justification of our ‘freedom belief’. I propose an account that (unlike most) does not lean heavily on our first-personal experience of choice and action, and instead regards freedom belief as a priori justified. I will then consider possible replies available toincompatibilists to the contention made by some compatibilists that the ‘privileged’ epistemic status of freedom belief (which my account endorses) supports a minimalist, and therefore compatibilist view of the nature of freedom itself.